2012
DOI: 10.4314/thrb.v14i4.2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tuberculosis drug resistance pattern among pulmonary tuberculosis patients with or without HIV infection in Mwanza, Tanzania

Abstract: Anti-tuberculosis drug resistance is a major problem in tuberculosis (TB) control, particularly multi-drug resistance TB (MDR-TB). The objective of this study was to determine the prevalence of primary and acquired anti-TB drug resistance among newly diagnosed pulmonary TB (PTB) and relapse cases. Sputa were collected from newly diagnosed and relapse PTB patients. Drug susceptibility tests (DST) were performed on sputum culture positive isolates of Mycobacterium tuberculosis using resistance ratio method on fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Studies have shown that previous TB drug exposure, especially in inadequate or inappropriate doses, can result in an increased risk of developing mono-drug or multidrugresistant tuberculosis [25][26][27][28]. The findings of this study of higher prevalence of MTB drug resistance among previously treated patients is consistent with findings of other Ugandan studies [25,29,30] and other neighbouring countries [4,31,32]. These high levels of drug resistance among previously treated patients raise concerns about TB treatment compliance and the successful application of drug resistance preventive measures such as directly observed…”
Section: Discussionsupporting
confidence: 88%
“…Studies have shown that previous TB drug exposure, especially in inadequate or inappropriate doses, can result in an increased risk of developing mono-drug or multidrugresistant tuberculosis [25][26][27][28]. The findings of this study of higher prevalence of MTB drug resistance among previously treated patients is consistent with findings of other Ugandan studies [25,29,30] and other neighbouring countries [4,31,32]. These high levels of drug resistance among previously treated patients raise concerns about TB treatment compliance and the successful application of drug resistance preventive measures such as directly observed…”
Section: Discussionsupporting
confidence: 88%
“…East African countries such as 5 in Ethiopia (Admassu, 2011 [ 23 ], Mekonnen et al, 2015 [ 24 ], Brhane et al, 2017 [ 25 ], Biresaw et al, 2018 [ 26 ], Girum et al, 2018 [ 27 ]), 2 in Kenya (Kerubo et al, 2016 [ 28 ], Huerga et al, 2017 [ 29 ]), 1 in Rwanda (Umubyeyi et al, 2007 [ 30 ]), 3 in Sudan (Eldin et al, 2011. [ 31 ], Sabeel et al, 2017 [ 32 ], Eldirdery et al, 2017 [ 33 ]), 2 in Tanzania (Chonde et al, 2010 [ 34 ], Range et al, 2012 [ 35 ]) and 3 in Uganda (Lukoye et al, 2011 [ 36 ], Lukoye, 2013 [ 3 ], Okethwangu et al, 2019 [ 37 ]) were used in this systematic review and meta-analysis indicated in S2 Table . The references of all 16 studies included for the meta-analysis are provided in supporting information ( S1 File ).…”
Section: Resultsmentioning
confidence: 99%
“…The overall prevalence of MDR-TB among previously treated TB cases was 21% (95%CI: 14–28%); I 2 = 99.1%, P≤0.001 [ Fig 5 ]. The prevalence of MDR-TB among previously treated TB cases of each of the studies included in this systematic review ranges from 1% (95%CI: -0.00–1.00) by Range et al [ 35 ] to 91% (95%CI: 81–101) by Okethwangu et al [ 37 ].…”
Section: Resultsmentioning
confidence: 99%